Administração pública e a arbitragem. Apreciação acerca da efetividade da referida técnica: estudo comparado entre o Estado do Maranhão e os Estados de São Paulo e Minas Gerais. - FALCÃO, Aileen Raphysa Sauaia (2019)
The present dissertation proposes to draw a comparative study on Arbitration, an appropriate means of dispute resolution, in the cases involving Public Administration in the States of Minas Gerais, São Paulo and Maranhão. Arbitration is nowadays a technique with great visibility in the Brazilian scenario, due to its regulation by Law 9.307 / 96 and subsequent modifications, among which, expressly allows the Public Administration to resolve the conflicts, in the which they appear as part, through arbitration. The perspective faced goes through the conception of effectiveness, in order to verify, from the criteria of economics, speed and specialization, its meanderings in the Brazilian states under study. With this purpose, information and data will be handled, based on a thorough bibliographical and documentary research on the subject.